Investigation of in vivo antidiabetic, analgesic, and CNS depressant properties of Lagerstroemia thorelli leaf extract - Rajib, Raisha (Brac University, 2024)
A thesis submitted to the School of Pharmacy in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.